Effect of cinnamate comonomers on the dental formulation properties. Issue 4 (14th May 2012) - Buruiana, Emil C.; Jitaru, Florentina; Melinte, Violeta; Buruiana, Tinca
Abstract This study reports the synthesis and characterization of two urethane dimethacrylates containing poly(ethylene oxide) or poly(propylene oxide) segment and cinnamate pendant moieties to be formulated in dental resin composites. 1H NMR, 13C NMR, and Fourier transform infrared spectroscopies, gel permeation chromatography, electrospray ionization‐mass spectroscopy, and thermogravimetric measurements confirmed their structure, whereas the photopolymerization evolution of oligodimethacrylates relating to a low–molecular‐weight dicinnamate methacrylate under ultraviolet irradiation was investigated by photo‐differential scanning calorimeter, monitoring the degree of conversion (DC) and polymerization rate. The photopolymerization results reveal that the investigated derivatives display a good photoreactivity (DC: ∼ 70%) during the formation of crosslinked polymers, the DC depending especially on the sample viscosity. The polymerization shrinkage for several mixtures including the urethane oligocinnamates (20 wt %) and diglycidyl methacrylate of bisphenol A/triethyleneglycol dimethacrylate system in the absence of filler was determined, the obtained values being in the range of 6.1–8.2 vol %. For few cured specimens incorporating quartz filler (75 wt %), water sorption/solubility, contact angle, and mechanical parameters were measured to establish if such monomers could be of interest in dentistry. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013